2014
DOI: 10.1093/rheumatology/keu285
|View full text |Cite
|
Sign up to set email alerts
|

Old medications and new targeted therapies in systemic sclerosis

Abstract: SSc is a multiorgan disease with significant morbidity that is associated with poor health-related quality of life. Treatment of this condition is often organ based and non-curative. However, there are newer, potentially disease-modifying therapies available to treat certain aspects of the disease. This review focuses on old and new therapies in the management of SSc in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 77 publications
1
52
0
4
Order By: Relevance
“…1 Although there has been significant progress over the years in identifying the early phases of the disease, and recognizing different clinical phenotypes with variable course, really effective therapy remains an unsolved issue. 2 The pathogenesis of SSc is still poorly understood, hence treatment of this condition is difficult and often 'organ-based'. Treatment options have targeted different pathogenic processes, including inflammation, immune dysregulation and fibrosis, showing only limited efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although there has been significant progress over the years in identifying the early phases of the disease, and recognizing different clinical phenotypes with variable course, really effective therapy remains an unsolved issue. 2 The pathogenesis of SSc is still poorly understood, hence treatment of this condition is difficult and often 'organ-based'. Treatment options have targeted different pathogenic processes, including inflammation, immune dysregulation and fibrosis, showing only limited efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no clinical trials on the isolated use of CYC in the therapy of skin induration. An analysis of results obtained in Scleroderma Lung Study-I, including 85 patients with dcSSc who were treated with CYC for 12 months, has shown a significant improvement and differences in modified Rodnan Skin Score (mRSS) compared to placebo [24]. There have been no randomized ból w klatce piersiowej, obrzęk śluzówek nosa oraz niedokrwistość [17].…”
Section: Skin Involvementmentioning
confidence: 99%
“…A prolowanego stosowania CYC w terapii stwardnień skóry. Przeprowadzona analiza wyników badania 85 chorych z dcSSc Scleroderma Lung Study-I, którzy otrzymywali CYC przez 12 miesięcy, wykazała znaczącą poprawę i różnice w modified Rodnan Skin Score (mRSS) w porów-naniu z placebo [24]. Nie ma randomizowanych badań klinicznych oceniających skuteczność MMF w zakresie redukcji nasilenia zmian skórnych ocenianych za pomocą mRSS, ale badania otwarte i retrospektywne wskazują, że MMF zmniejszał stwardnienia skóry w przebiegu dcSSc [25].…”
Section: Scleroderma Renal Crisisunclassified
“…Unfortunately, controlled studies analyzing the effects of different maintenance therapies such as azathioprine or mycophenolate mophetil (MMF) after CYC treatment are not available. In addition, the optimal treatment duration with CYC is not known [77].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Three controlled trials on HSCT in SSc have been published so far [77]. The Autologous Stem Cell Transplantation International Scleroderma (ASTIS) Trial revealed that HSCT-treated patients had significant better long-term event-free survival (defined as death or major organ failure), with the cost of a higher treatment-related mortality in the first year after therapy.…”
Section: Other Emerging Treatments-biologics and Stem Cell Transplantmentioning
confidence: 99%